The Ordo salutis in Pontoppidan's 1737: Explanation of Luther's Small Catechism - Austad, Torleiv (Lutheran quarterly, 2025)
In 1736 Christian VI, who reigned as king of Denmark and Norway from 1730 until 1746, introduced confirmation for everyone between the ages of fifteen and nineteen. This called for instruction in the Christian faith to endow the confirmands with knowledge and guidance to lead them to a personal confirmation of the grace they had received in baptism. Royal chaplain Erik Ludvigsen Pontoppidan the Younger (1698-1764) was assigned the task of writing an explanation of Luther's Small Catechism in the light of the king's Pietist ecclesiastical politics. He published his catechetical explanation under the title Sandhed til Gudfrygtighed (Truth unto Godliness) in 1737. By royal decree it was approved for general use the following year. The central theme of the Explanation is the "order of sanctification," indeed "the correct order" for the appropriation of salvation. The Explanation was especially intended for adults who had been baptized as infants but whose faith had withered or died. The understanding of Pontoppidan's formulation of the order of sanctification from a Lutheran perspective is discussed in the present article.